Optimal age to begin with Greco-Roman wrestling and reach peak performance - trends in cases of world-class medal winners of various weight groups - Karnincic, H.; Baic, M.; Sprem, D. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
When to start doing Greco-Roman wrestling? How many years of experience are needed to accomplish world-class standard and achievements? At which age do wrestlers nowadays win their world championship or Olympic medals? What age-related trends can be observed in wrestlers of different weight groups? This study explored all these questions. PURPOSE: The aim of the research was to determine differences between weight groups in age-related parameters (beginning age, wrestling experience, and peak performance age) of world-class top-level wrestlers and to analyse the revealed trends. METHODS: The sample of entities (N=299) comprised wrestlers who won their first World Championship or Olympic Games` medals in the period 2002-2015. The sample of variables consisted of three age-related parameters: Beginning, Experience and Peak. The variables were processed by descriptive statistics. The differences between weight groups were analysed using the Kruskal-Wallis test and trends were added to graphical representation to perform analysis across years. RESULTS: Olympic Games or world championship (OG/WCh) medal winners started their wrestling training at the age of 10.51±2.98 years. They had been training for 15.09±4.28 years before they won their first medal at the age of 25.55±3.10 years. The middleweight wrestlers started to train wrestling significantly earlier (p<0.01), than their lightweight counterparts and most heavyweight counterparts and thay acquired more wrestling experience before the first OG/WCh medal winning. CONCLUSIONS: The wrestling beginning age demonstrated a decreasing trend across the years of the observed period, so caution is advisable as regards early specialization. A rising trend in training experience is a consequence of a declining trend in wrestling beginning age. Analysis across weight groups indicated, although not pronouncedly, that lightweight- and heavyweight-group wrestlers may begin to train at later age and accomplish outstanding achievements with less experience. This study provides a precise set of information to wrestling coaches on when to include their trainees in wrestling, for how long one needs to wrestle before winning the first medal and at which age we can expect a wrestler to win his/her first major competition (WCh or Olympic) medal in accordance with the respective weight groups.